Affective design for evaluation instruments of agro-industrial training performance - Zahra Yuniarti; Didik Purwadi; Mirwan Ushada (AGROINTEK, 2026)
Affective design incorporates emotional and subjective aspects into product design to enhance user satisfaction. To design a performance evaluation instrument that aligns with user needs, Kansei engineering offers a method for translating subjective user preferences into tangible design element. This study aims to (1) identify user needs in the instructor performance evaluation attribute and (2) extract essential factors for developing performance evaluation instruments in agro-industrial training institutions. The input dataset was obtained through interview to acquire Kansei words. Data were collected and subsequently reduced through a Kansei word selection questionnaire, Aiken’s test, and a semantic differential scale. Factor analysis was conducted to identify the attributes of performance evaluation and to extract the features necessary for the development of the instrument. As the result, the collected Kansei words related to performance evaluation attribute will be instructor competency, clarity of content, guiding participants, capability to answer, well dressed, punctuality, broadening perspectives, mutual support, respect and helpful. As for the feature considerations to develop the instrument, Kansei words used are online, substantive, on point, click and go, and measurable. The results of this study demonstrate the applicability of Kansei engineering in designing affective performance evaluation instruments that align with user needs.